2015
DOI: 10.1182/blood-2015-07-658872
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and outcome of light chain deposition disease

Abstract: Key Points Deep clonal responses to chemotherapy are associated with improved renal and overall outcomes in patients with light chain deposition disease. Deep clonal responses should be targeted, even in patients with advanced chronic kidney disease from light chain deposition disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
128
4
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(146 citation statements)
references
References 24 publications
10
128
4
4
Order By: Relevance
“…Fortunately, the hematologic response can be improved by the addition of autologous stem cell transplant. Achievement of VGPR in monoclonal Ig deposition disease similarly has been found to improve renal and patient survival (21,42,74,89). Kidney transplant has been successfully performed in patients with hematologic complete response without recurrence.…”
Section: Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…Fortunately, the hematologic response can be improved by the addition of autologous stem cell transplant. Achievement of VGPR in monoclonal Ig deposition disease similarly has been found to improve renal and patient survival (21,42,74,89). Kidney transplant has been successfully performed in patients with hematologic complete response without recurrence.…”
Section: Managementmentioning
confidence: 99%
“…Bortezomib seems to be the most effective agent in monoclonal Ig deposition disease (21,42,74,89). In one study, immunomodulatory drugs represented by thalidomide and lenalidomide were found to be less effective in achieving VGPR or better responses (21). Fortunately, the hematologic response can be improved by the addition of autologous stem cell transplant.…”
Section: Managementmentioning
confidence: 99%
See 3 more Smart Citations